TANTANGAN AKSESBILITAS INFORMASI DAN SISTEM BAGI PENYANDANG DISABILITAS DALAM KONTESTASI PEMILU 2024: PERSPEKTIF PLURALISME AGONISTIK - Indriyany, Ika Arinia; Praceka, Puspita Asri; Aini, Hilyatul (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This research draws on the experience of a disabled legislative candidate in the 2024 elections. The primary challenge faced was the lack of accessible information and systems provided by the government and election organizers. Using a narrative approach along with the Agonistic Pluralism framework, this study examines the interactions, continuity, and dynamics of Sikdam's campaign within a context of limited accessibility. The findings show that, although the Aceh Independent Election Commission has conducted outreach on inclusive elections, significant gaps remain in providing accessible information and election systems that support full participation by persons with disabilities. Sikdam faced difficulties obtaining campaign materials in formats accessible to people with disabilities (such as Braille) and lacked information about election procedures and stages adapted for persons with disabilities. These barriers, worsened by low public awareness, reveal a paradox between inclusive regulations and their practical implementation. The study suggests that Sikdam’s narrative successfully initiated an agonistic dialogue on inclusivity, exposing systematic flaws in ensuring accessible information and systems, and stressing the need for stronger affirmative Policy reforms. The theoretical implications presented in this research are: (1) there should be a more inclusive political party model, as political parties have so far failed to serve as effective mediators that balance the demands of inclusiveness and electoral structure; (2) the electoral system provides both a space for the reproduction of inequality and a space for resistance; (3) the model of agonism through institutionalized political conflict is crucial for the legitimacy of democracy